Nonsurgical Treatment of Peri-Implantitis: Case Series - Ekaterina Diachkova; Stefano Corbella; Silvio Taschieri; Svetlana Tarasenko (MDPI AG, 2020)
Peri-implantitis is one of the most important biological complication of dental implants. It has inflammatory nature, proved association with plaque accumulation in peri-implant tissues, and can be progressive on background of several factors, like comorbidity factors and bad habits. The prophylaxis and different methods of treatment were discussed during last 30 years, and surgical and nonsurgical techniques have their foes, benefits, and disadvantages. In this article, we describe the case series of various nonsurgical treatments of peri-implantitis with the use of protocols based on the application of local antibiotics (doxycycline, lincomycin, and erythromycin), mechanical and chemical debridement of dental implant surface, and mini-invasive regenerative technique with injections of bovine collagen. All these three cases demonstrated good results with the maintenance of bone level and absence of clinical signs of inflammation for at least a year according to the X-ray imaging (bone defect volume) and clinic assessments (probing depth, bleeding or suppuration, mucosa color, and pain presence).